Initiation in sport under the approach of motor praxiology (Impetus, 2021)
Sports initiation processes play a very important role in the proper development of the stages of maturation, interaction and growth of the children who experience them. It is through these that certain types of “behaviors” or intelligences begin to develop that in the future will end up being decisive in the structural formation of the life of human beings. However, these initiation processes in motor practices are often not seen as essential or essential by parents, or are not possible in some low-income households, or what is more common, they are developed from bets very specific or sporting that tend to limit the motor experiences of children, preventing them from developing their capacity for exploration and Discovery.